LITERASI DAN MODEL MANAJEMEN KEUANGAN UMKM BERBASIS DIGITAL PADA UMKM-UMKM DI KABUPATEN BOALEMO PROVINSI GORONTALO - Sukrianto Sukrianto Namrud (Pusat P2M Politeknik Negeri Batam, 2021)
In 2015 to 2020 UMKM in Boalemo Regency have experienced ups and downs. This is a problem of decline, one of the main reasons is that UMKM have not been able to survive with their capital. The purpose of the research is to provide knowledge to community groups/micro and small and medium enterprises (UMKM) about literacy and digital-based UMKM financial management models, and to be able to increase the participation of community groups/UMKM in managing UMKM through the provision of knowledge about digital-based management. Descriptive research method with a qualitative approach. The results showed that UMKM in Boalemo District experienced problems in running their businesses, especially during the pandemic due to the lack of government attention in helping UMKM in Boalemo District. The average UMKM in Boalemo Regency in the use of financial literacy fully understands the development of digital-based UMKM, especially in increasing income, even their education level in managing good financial management and digitally still relies on manual recording. While the digital-based UMKM financial management model is not in accordance with the targets and objectives. This is evidenced by UMKM business actors who have not been able to make financial reports. UMKM in Boalemo Regency have not been able to use information technology and social media, especially in utilizing digital based financial management designs. This is because UMKM only rely on manual recording. Keywords: Literacy, Model, Financial Management and UMKM